Are They Complying? Physicians' Knowledge, Attitudes, and Readiness to Change Regarding Low Back Pain Treatment Guideline Adherence. Issue 4 (15th February 2017) - Epstein-Sher, Sheera; Jaffe, Dena H.; Lahad, Amnon
Abstract : Study Design: Cross-sectional survey of 145 primary care practitioners (PCPs). Objective: To examine low back pain (LBP) guideline knowledge, readiness to implement (RTI) these guidelines, and LBP attitudes and beliefs among Israeli PCPs and determine whether physician age, guideline familiarity, and medical specialty affect these variables. Summary of Background Data: LBP is a common condition managed primarily by PCPs. Little is known, however, about physician's LBP knowledge, attitudes, and beliefs and how these factors (knowledge, A&B) influence their practice behavior. Knowledge, attitudes, and beliefs of PCPs have been shown to influence the course of their patients' LBP, and guidelines were devised in an attempt to improve the effectiveness and quality of LBP care. Research worldwide and in Israel has shown that LBP guideline implementation is not yet optimal. Methods: Participants completed a questionnaire. Variables were measured using a translated, validated version of the Health Care Providers' Pain and Impairment Relationship Scale; demographic and professional characteristics were analyzed for correlation with the outcome variables. Results: The likelihood of PCPs having nonguideline-consistent attitudes and beliefs (A&B) was greater among those older than 50 years ( P  < 0.05). Family medicine specialists (family practitioners [FPs]) were more likely to have a high level of guideline knowledge as compared to nonfamily medicine specialists (general practitioners (83.8 vs. 61.9, respectively; P  < 0.001). Differences between FPs and general practitioners were also observed for the mean Health Care Providers' Pain and Impairment Relationship Scale score (34.6 vs. 41.1, respectively, P  = 0.00), indicating a higher consistency of attitudes and beliefs with guidelines among FPs. No significant association was found between PCPs' knowledge level and RTI the guidelines. Conclusion: The present study showed that PCPs, especially FPs, had high levels of LBP guideline knowledge, although RTI was limited. The need for greater exposure to and understanding of the importance of implementation of LBP guidelines is essential for future guideline adherence. Level of Evidence: 3